2018
DOI: 10.1007/s00246-018-1955-z
|View full text |Cite
|
Sign up to set email alerts
|

Search of Somatic Mutations of NKX2-5 and GATA4 Genes in Chinese Patients with Sporadic Congenital Heart Disease

Abstract: Congenital heart disease (CHD) usually occurs sporadically, with only a minority of cases associated with a known genetic mechanism. Cardiac-specific transcription factors NKX2-5 and GATA4 play key roles in the mammalian heart development, and the affected cardiac tissues of CHD patients are prone to somatic mutations which thus participate in the pathogenesis of CHD. We collected 98 patients with sporadic CHD, extracted genomic DNA from cardiac tissues and blood, and then screened NKX2-5 and GATA4 genes using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Previous study found in the tissues of heart and blood, one recognized single‐nucleotide polymorphism (SNP) (rs2277923) in NKX2‐5 and one recognized SNP (rs56166237) in GATA4 . In contrast to our study, their study presented that NKX2‐5 and GATA4 mutations have no role in sporadic CHD pathogenesis (Yin et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous study found in the tissues of heart and blood, one recognized single‐nucleotide polymorphism (SNP) (rs2277923) in NKX2‐5 and one recognized SNP (rs56166237) in GATA4 . In contrast to our study, their study presented that NKX2‐5 and GATA4 mutations have no role in sporadic CHD pathogenesis (Yin et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Esposito et al ( 104 ) utilized freshly frozen cardiac tissue samples of right ventricular myocardium and matched blood samples from nine cases undergoing surgical treatment for TOF and 24 patients with left heart hypoplasia to evaluate the incidence of somatic GATA4 mutations in heart tissue by direct sequencing analysis; no somatic or germline mutations were identified. Yin et al ( 105 ) performed direct PCR-sequencing analysis of GATA4 on genomic DNA purified from heart tissue and peripheral blood cells of 98 cases with sporadic congenital heart disease and found two well-known SNPs (rs3729856 and rs56166237) in GATA4 in both heart tissue and blood samples, indicating a role of germline GATA4 variations in development of congenital heart disease. Given these conflicting reports on the contribution of somatic mutations to congenital heart disease, the finding of a somatic mutation of GATA4 in a case of TOF is rare and may depend on various factors such as analytical methods, ethnicity and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our association analysis, a previous study identified that the rs2277923 SNP on the NKX2-5 gene is linked to the sporadic ASDs in the Chinese Yunnan population and the A allele of rs2277923 is a potential risk factor resulting in ASDs [ 5 ]. Nevertheless, there are some different outcomes in CHD studies, which presented that rs2277923 has no role in sporadic CHD pathogenesis in Chinese patients [ 21 , 22 ]. The opposite research results may be related to the races and region differences.…”
Section: Discussionmentioning
confidence: 99%